Towards a harmonized bronchopulmonary dysplasia definition: a study protocol for an international Delphi procedure - Martin Offringa; Anton H van Kaam; Wes Onland; Prakesh S Shah; Erik A Jensen; Rosemary D Higgins; Trixie A Katz; J Jane Pillow; Tetsuya Isayama; Benjamin Stoecklin; Sanne J Gordijn; Eduardo Bancalari; et al. (BMJ Publishing Group, 2023)
Introduction Bronchopulmonary dysplasia (BPD) remains the most common complication of preterm birth with lifelong consequences. Multiple BPD definitions are currently used in daily practice. Uniformity in defining BPD is important for clinical care, research and benchmarking. The aim of this Delphi procedure is to determine what clinicians and researchers consider the key features for defining BPD. With the results of this study, we hope to advance the process of reaching consensus on the diagnosis of BPD.Methods and analysis A Delphi procedure will be used to establish why, when and how clinicians propose BPD should be diagnosed. This semi-anonymous iterative technique ensures an objective approach towards gaining these insights. An international multidisciplinary panel of clinicians and researchers working with preterm infants and/or patients diagnosed with BPD will participate. Steering committee members will recruit potential participants in their own region or network following eligibility guidelines to complete a first round survey online. This round will collect demographic information and opinions on key features of BPD definitions. Subsequent rounds will provide participants with the results from the previous round, for final acceptance or rejection of key features. Statements will be rated using a 5-point Likert scale. After completing the Delphi procedure, an (online) consensus meeting will be organised to discuss the results.Ethics and dissemination For this study, ethical approval a waiver has been provided. However, all participants will be asked to provide consent for the use of personal data. After the Delphi procedure is completed, it will be published in a peer-reviewed journal and disseminated at international conferences.